2017
DOI: 10.18632/oncotarget.18710
|View full text |Cite
|
Sign up to set email alerts
|

ESE-1/ELF3 mRNA expression associates with poor survival outcomes in HER2+ breast cancer patients and is critical for tumorigenesis in HER2+ breast cancer cells

Abstract: ESE-1/Elf3 and HER2 appear to establish a positive feedback regulatory loop, but the precise role of ESE-1 in HER2+ breast tumorigenesis remains unknown. Analyzing public repositories, we found that luminal B and HER2 subtype patients with high ESE-1 mRNA levels displayed worse relapse free survival. We stably knocked down ESE-1 in HER2+ luminal B BT474 cells and HER2 subtype SKBR3 cells, which resulted in decreased cell proliferation, colony formation, and anchorage-independent growth in vitro. Stable ESE-1 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…For instance, overexpression of ELF3 in lung cancer, HER2+ breast cancer, and liver cancer can facilitate the progression of tumors. [11][12][13] However, a previous study showed that loss of ELF3 induces epithelial to mesenchymal transition in ovarian cancer, indicating that ELF3 acts as a tumor suppressor. 34 It has also been demonstrated that overexpression of ELF3 in the cholangiocarcinoma cell line can significantly inhibit its proliferation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, overexpression of ELF3 in lung cancer, HER2+ breast cancer, and liver cancer can facilitate the progression of tumors. [11][12][13] However, a previous study showed that loss of ELF3 induces epithelial to mesenchymal transition in ovarian cancer, indicating that ELF3 acts as a tumor suppressor. 34 It has also been demonstrated that overexpression of ELF3 in the cholangiocarcinoma cell line can significantly inhibit its proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Then, the E74-like ETS transcription factor 3 (ELF3) gene was recognized as the target of miR-1224-5p based on integrated bioinformatic analysis and experimental verification. ELF3 plays an important oncogenic role in several tumors, such as lung cancer, 11 liver cancer, 12 and breast cancer, 13 via the PI3K/AKT, ERK and EMT signaling pathways. To further investigate the specific functions of ELF3 in pancreatic cancer, Kyoto encyclopedia of genes and genomes (KEGG) pathway, gene ontology (GO), and gene set enrichment analysis (GSEA) studies were performed based on the TCGA and STRING databases.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, ELF3 may have a pro-tumorigenic role in HER2 + tumours, where ELF3 is upregulated due to HER2-signaling driven activation of the ELF3 promoter [ 37 , 38 ]. HER2 + breast cancers with high ELF3 mRNA expression have a worse outcome, and ELF3 knockdown in HER2 + breast cancer cell lines attenuated tumour growth through inhibition of AKT signaling [ 39 ]. ELF3 knockdown also inhibited the growth in HER2 + trastuzumab-resistant breast cancer cell lines [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…ESE-1 belongs to the ETS family of transcription factors and has been associated with cancer progression. 6,7 However, its observed effects are controversial 9,18,19,22,[24][25][26][27][28][29][30]32,40,41 ; whether ESE-1 is oncogenic or tumor suppressive has not been clearly determined in colon cancer or in any other type of cancer using an in vivo mouse model. Since inflammatory bowel disease (IBD)-related carcinogenesis is a very common pathological and clinical aspect of colon cancer, we adopted an AOM-induced and DSS-promoted colon cancer model using ESE-1 knockout mice, which may potentially be more susceptible to colonic inflammation and neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…16 The ESE-1 gene locus (1q32.1) is amplified in 50% of early human ductal carcinoma cases, and overexpressed in HER2/neu activated breast cancer cells. 9,17 ESE-1/ ELF3 mRNA expression is associated with poor survival outcomes in HER2 + breast cancer patients 18 and promotes epithelial-mesenchymal transition (EMT) in breast cancer cells. 19 These data suggest a tumor promoting role for ESE-1.…”
mentioning
confidence: 99%